Measuring the Productivity of Tourism Sector in Indonesia - Muhammad Syafii; Mimma Maripatul Uula (Halal Tourism and Pilgrimage, 2022)
This study aims to measure tourism productivity in Indonesia using the Malmquist Productivity Index (MPI) method with the 2010-2020 research period. The research object used is 34 provinces in Indonesia. The data for this research comes from the annual APBD report in each province. The input variables in this study are the economic sector budget and the tourism and cultural budget. While the output is tourism and culture. The results of this study explain that during the 2015-2020 period, the productivity level of provincial tourism in Indonesia has a fluctuating trend from year to year. Based on the average TFPCH score, it is concluded that tourism productivity has shown a decline and technological change has not contributed optimally to increasing tourism productivity in Indonesia. Furthermore, tourism productivity when the Covid-19 pandemic occurred was still declining. Then, analysis of the Malmquist Index quadrant shows that the provinces of Indonesia dominate quadrant 3, namely 22 provinces, which are then followed by quadrant 4 with a total of 12 provinces.